Implementasi Manajemen Kewirausahaan dalam Meningkatkan Life Skill Santri di Pondok Pesantren Fathul Ulum Diwek Jombang - Sunardi Sunardi; Sohib Sohib (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
Seeing in the era of globalization that encourages the rapid development of science and technology, of course a boarding school is required to follow these developments. Edially, pondok pesantren does not only maintain its traditional way to develop the mindset, personality and future of its students. However, it takes extra strength from all outside parties in order to further improve the quality of students, both in the religious, intellectual, and even life skills that are qualified for the students. Because in the world of education is a very basic supporting factor for the change and progress of a society. The results of research on the form of entrepreneurship in the Fathul Ulum Diwek Islamic Boarding School Jombang are in the Culinary Sector, the Agriculture Sector, the Fisheries Sector, the Printing Sector, the Sewing Sector. The Entrepreneurship Management Implementation Process in improving the life skills of the students is through planning. organizing Actuating controlling (PAOC).